Inter-Group Disparities in Fatal Road Traffic Accident in Texas - Iyanda, Ayodeji (European Scientific Journal, ESJ, 2018)
The risk of dying from a road accident is higher than dying from heart and infectious diseases. Mortality and injury related to fatal accident is increasing partly due to the level of motorization. Further, the associated risk of accident varies among diverse population groups. This study examines the inter-group difference in injury and mortality caused by road accident in Texas using Fatality Analysis Reporting System (FARS), the nation’s most comprehensive population-based accident database from 2014 to 2016. Texas had the highest accident mortality in 2016 making accident the fifth leading cause of death. This study performed two main tasks: 1) It analyzed injury severity variation for different age groups using data mining technique. 2) Accident fatality disparity was determined by using both nonparametric version of analysis of variance and multilevel binary logistic regression. The study interprets fatality risk using the odd ratio. Result shows that Asian subgroups, European Spanish, Central and South Americans, and children were at greater risk. This study is important for culturally specific public health intervention design targeting the most vulnerable subgroups based on people’s cultural orientation.